Existence of service consumption service paid in sociological perspective - Misdela Firma Sari; Fatmariza Fatmariza; Maria Montessori (Fakultas Ilmu Pendidikan UNP)
The purpose of this article is to explain the existence of paid consumption services in the midst of people's lives. This research uses qualitative research approach with descriptive type. Researchers found that the presence of paid consumption services in the midst of people's lives is considered very effective and efficient in terms of time and energy, this is considering the many people who live wander for both education and work. However, indirectly, the presence of paid consumption services fades the social values, the sincerity in work and the spirit of mutual cooperation begins to fade and turn into a wage system that is like making the consumption and serving the guests by way of being hired. On the other hand it also affects kinship relations.